ANALISA PENGARUH KETINGGIAN HIDROFOIL NACA 4412 TERHADAP HAMBATAN PADA LAMBUNG KAPAL DTMB 5415 - Irfan Izzulhaq (2022)
Current research for ship fuel efficiency is divided into four areas of research: engine efficiency, propulsion efficiency, sustainable alternative resources, and reduced drag in the hull (Uithof1, 2015). The resulting resistances of the ship's hull are total resistance, wave-making resistance and friction. The shape of the ship affects the value of resistance, hence much of the innovation in hull forms that have been carried out to date, such as bulbous bow, transom sterrn, catamaran hull, trimaran, and so forth which is intended as an energy saving device. This research is implementing hydrofoil with a sinkage variation of NACA on the hull of destroyer DTMB 5415 model. Begin with modeling of the hull of the DTMB5415 model, variating on the sinkage of NACA 4412 (rhodesg32-il) at the deployment of the port at trailing edge draft 0,02 m, 0,04 m, 0,06 m, 0,08 m and 0,1 m and 0,085 m trailing edge AP. Calculation and analysis using CFD methods for the component resistances. The results of the CFD analysis of various sinkage of the NACA will be compared to the impact of the component of the resistance and will be drawn into conclusions of variations showing the lowest and most efficient response to the value of resistance. Based on the simulation, the model is obtained with NACA 4412 (rhodesg32-il) at the sinkage trailing edge draft 0,04 m has the lowest value of total resistance.